Electrochemical Dealloying of Bimetallic ORR Nanoparticle Catalysts at Constant Electrode Potentials. Issue 4 (1st January 2015) - Rudi, Stefan; Gan, Lin; Cui, Chunhua; Gliech, Manuel; Strasser, Peter
Abstract : Dealloyed, that is, selectively leached Pt-based oxygen reduction reaction (ORR) nanoparticle catalysts have demonstrated previously unachieved initial reactivity and performance durability in single cell of PEM fuel cells. Dealloying is typically achieved using free corrosion in acid or electrochemical cycling. Here, we explore dealloying at constant electrode potentials of PtNi3 bimetallic alloy nanoparticles at 5–7 nm and >20 nm size ranges. We investigate how Ni dissolution at four distinct electrode potentials affects the composition, morphology, and surface roughness of the resulting dealloyed catalysts. The electrode potentials cover the hydrogen-adsorption, the double layer region, and the oxygenate adsorption region to examine whether adlayers affect the characteristics of the dealloyed catalysts. We show that large alloy nanoparticles invariably dealloy into porous nanoparticles with a relatively low Ni molar ratio of 0.4, while the smaller size particles show non-porous solid core-shell structures with a monotonic dependence between Ni at% and potential. We provide evidence that the dealloyed catalyst surface is strongly influenced by the presence/absence of adsorbed adlayers of hydrogen or oxygenates. In particular, data suggest that adsorbate adlayers modify the balance between Ni dissolution and Pt surface diffusion during the dealloying process resulting in rougher catalyst surfaces with enhanced surface area values.